A review on research progress in the direct synthesis of hydrogen peroxide from hydrogen and oxygen: noble-metal catalytic method, fuel-cell method and plasma method. Issue 6 (8th January 2016) - Yi, Yanhui; Wang, Li; Li, Gang; Guo, Hongchen
Abstract : The direct synthesis of H2 O2 from H2 and O2 using Pd catalyst, fuel cell and plasma methods have been reviewed systematically. Abstract : Hydrogen peroxide (H2 O2 ) as a highly efficient and green oxidant has become one of the 100 most important chemicals in the world. Some current research progress in the direct synthesis of H2 O2 from H2 and O2 by noble-metal catalyst, fuel cell and plasma methods has been reviewed systematically in this paper. Perspectives about the development direction and application prospect of the above-mentioned three methods have also been discussed.